(untitled) (Harmoni, 2013)
As a discipline, anthropology raised ΓÇÿcultureΓÇÖ as a central concept that is widely discussed. In the process, ΓÇÿcultureΓÇÖ has very interesting dynamics, especially when used as an analytical tool in assessing change and religion issues. This paper argues about the dialectic of culture, change, and religion issues so that can explain the phenomena that observed in our daily lives. Through literatures and observation method, this paper aims to provide a perspective to understand the meaning of a phenomenon that observed and analyzed through the reveal of ΓÇÿhidden transcriptΓÇÖ behind the phenomenon.